The breakthrough of educational technology in the Algerian EFL classroom ( blended learning ) - BELABED, Nassrine Safia (My University, 2020)
As the educational system in Algeria has undergone many changes and improvements, especially after the adoption of competency-based approach in teaching methods in 2003, people continue to ask for more investment in educational technology. This interest is due to the need to change and improve the quality of education. The aim of this study is to first explore the views of Algerian middle schools on the use of ET tools by EFL teachers in their classes. A hybrid method based on questionnaires was used. The results show that EFL teachers were aware of ET in the EFL teaching and learning. In addition, the survey results show that most teachers use computers and data projectors to teach English. Besides, The findings showed that teachers believe that incorporating ET into teaching is a source of motivation for their students. In addition, it is reported that the lack of ET tools and the lack of training and support to integrate them are the main obstacles that prevent middle school EFL teachers from successfully integrating these resources in the classroom. It is highly recommended to train in ICT integration, technical support and ethyl tools in middle schools in Algeria to overcome ET barriers.
The Case study of Firth Year Middle School in Mostaganem
Keywords: Algerian education; CBA; EFL; ET; ICT